Forging Egypt's Golden Generation: Crafting Curriculum Excellence for ABA Kindergarten in Cairo, Egypt - Mahasri Shobahiya; Nurul Latifatul Inayati; Alfiyatul Azizah; Junita Dwi Wardhani; Muhtadi Muhtadi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The management and development of Aisyiyah Bustanul Athfal Kindergarten (TK ABA) Cairo is still needs to be improved. Meanwhile, currently the ABA Cairo Kindergarten is the only Indonesian private kindergarten in Egypt and is a reference for early childhood education for the Indonesian people in Cairo. The fundamental problem faced by ABA Cairo Kindergarten is that it doesn’t have a standard curriculum document that promotes the advantages and characteristics of the stake holders in the education unit. The purpose of this International Collaborative Community Service (PkM-KI) activity is to assist in the preparation of curriculum documents that are adapted to the spirit of an independent curriculum. This PkM implementation method uses a Participatory Action Research (PAR) approach, by actively involving partners in the participation and action dimensions. The target for the implementation of this PkM is the compilation of the ABA Cairo Kindergarten curriculum document. The result of this PkM KI is the arrangement of curriculum document which was legalized by the competent authority. Keyword : Accompaniment, curriculum document, Aisyiyah Bustanul Athfal Kindergarten, Golden generation. Abstrak Pengelolaan dan pengembangan Taman Kanak-kanak ‘Aisyiyah Bustanul Athfal (TK ABA) Kairo masih sangat perlu ditingkatkan. Sedangkan pada saat ini TK ABA Kairo merupakan TK swasta Indonesia satu-satunya yang ada di negara Mesir dan merupakan rujukan bagi Pendidikan anak-anak usia dini bagi masyarakat Indonesia Kairo. Permasalahan mendasar yang dihadapi oleh TK ABA Kairo, yaitu belum memiliki dokumen kurikulum baku yang mengunggulkan kelebihan dan ciri khas stake holder satuan Pendidikan tersebut. Tujuan kegiatan Pengabdian kepada Masyarakat Kolaborasi Internasional (PkM-KI) ini adalah mendampingi penyusunan dokumen kurikulum yang disesuaikan dengan spirit kurikulum merdeka. Metode pelaksanaan PkM ini menggunakan pendekatan Participatory Action Research (PAR), dengan melibatkan mitra secara aktif dalam partisipasi dan dimensi aksi. Target capaian pelaksanaan PkM ini yaitu tersusunnya dokumen kurikulum TK ABA Kairo. Hasil PkM KI ini adalah tersusunnya dokumen kurikulum pencetak generasi emas yang disahkan oleh pejabat berwenang. Kata Kunci: Pendampingan, dokumen kurikulum, TK ABA, generasi emas